Dielectric study on hierarchical water structures restricted in cement and wood materials. (20th February 2017) - Abe, Fumiya; Nishi, Akihiro; Saito, Hironobu; Asano, Megumi; Watanabe, Seiei; Kita, Rio; Shinyashiki, Naoki; Yagihara, Shin; Fukuzaki, Minoru; Sudo, Seiichi; Suzuki, Youki
Abstract: Dielectric relaxation processes for mortar observed by broadband dielectric spectroscopy were analyzed in the drying and hydration processes for an aging sample in the frequency region from 1 MHz up to 2 MHz. At least two processes for structured water in the kHz frequency region and another mHz relaxation process affected by ionic behaviors were observed. Comparison of the relaxation parameters obtained for the drying and hydration processes suggests an existence of hierarchical water structures in the exchange of water molecules, which are originally exchanged from free water observed at around 20 GHz. The water molecules reflected in the lower frequency process of the two kHz relaxation processes are more restricted and take more homogeneous structures than the higher kHz relaxation process. These structured water usually hidden in large ionic behaviors for wood samples was observed by electrodes covered by a thin Teflon film, and hierarchical water structures were also suggested for wood samples. Dielectric spectroscopy technique is an effective tool to analyze the new concept of hierarchical water structures in complex materials.